High-strength composite modified emulsified asphalt material as well as preparation method and application thereof
By using aqueous epoxy resin in emulsified bitumen and composited with alkaline silica sol to form a three-dimensional crosslinking network and refined particles, the problem of insufficient layering and compatibility of emulsified bitumen materials at high temperatures is solved, and higher strength, stability and temperature resistance are achieved.
Patent Information
- Application Number
- CN202411705949.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
Discontinuous stirring of existing emulsified asphalt materials at high temperatures leads to stratification and isolation, and the compatibility of polymer modifiers with asphalt binding materials is limited, resulting in insufficient performance.
The aqueous epoxy resin is combined with an alkaline silica sol to form a three-dimensional crosslinking network through the crosslinking reaction of the aqueous epoxy resin and emulsified bitumen, and the emulsified bitumen particles are refined through the silica sol to enhance the interaction between the particles.
It significantly improves the bonding force, stability, compressive strength and shear strength of emulsified asphalt, optimizes the microporosity, enhances waterproofing performance, and improves high and low temperature resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road materials, and in particular to a high-strength composite modified emulsified asphalt material and a preparation method and application thereof. Background Art
[0002] Traditional emulsified asphalt materials have gradually exposed some performance defects, such as poor durability, insufficient high temperature resistance, high brittleness at low temperatures, etc. In order to overcome these shortcomings, various types of modified asphalt materials have been widely studied and applied in recent years, among which the most representative modification method is modification by adding polymers or other inorganic materials.
[0003] Modifiers for emulsified asphalt can be divided into three categories according to their chemical structure and properties: elastomers, plastomers and polymer materials with reactive groups. Currently commonly used polymer modifiers are generally physically blended with asphalt binders without significant chemical changes. In addition, there are certain differences in molecular weight, density, structure and other properties between asphalt binders and polymer modifiers. It is difficult to form a stable thermodynamic system between polymer modifiers and asphalt binders, so their compatibility is limited, and discontinuous stirring at high temperatures will lead to stratification and segregation. Therefore, several commonly used polymer-modified emulsified asphalts have deficiencies in production, storage, economy, performance and other aspects. For example, the SBS modified asphalt binder has high viscosity and is difficult to emulsify; the high temperature stability of SBR modified asphalt is not ideal.
[0004] A water-based additive is a polymer in a water system that is stabilized in water by surfactants or self-emulsified by the attachment of hydrophilic polar groups. As the water evaporates, the polymer droplets gradually coalesce, initiating a self-crosslinking reaction, and then forming an interconnected polymer network. A self-crosslinking water-based emulsion is a type of material that can be added to emulsified asphalt to improve its performance. Among them, water-based epoxy resin can effectively improve the thermal stability and adhesion of SBR modified emulsified asphalt, but its low-temperature performance is poor. Nano-SiO2 can effectively improve the low-temperature performance of emulsified asphalt, so the use of the two composites is expected to simultaneously improve the comprehensive performance of emulsified asphalt.
[0005] However, when epoxy resin and silica sol are combined to modify emulsified asphalt, how to ensure the compatibility of the two materials is a technical problem. If the two are not well compatible, it may lead to poor modification effect, or even problems such as material separation and precipitation, affecting the overall performance of asphalt. Therefore, how to use epoxy resin and silica sol in combination to improve the strength of emulsified asphalt is a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0006] In order to solve the problem mentioned in the above background on how to use epoxy resin and silica sol in combination to improve the strength of emulsified asphalt, the present invention provides a high-strength composite modified emulsified asphalt material and a preparation method and application thereof.
[0007] The high-strength composite modified emulsified asphalt material provided by the present invention comprises, by weight percentage, 50%-70% of base asphalt, 1%-3% of emulsifier, 5%-15% of water-based epoxy resin, 5%-15% of curing agent, 0.1%-0.3% of stabilizer, 3%-10% of alkaline silica sol, and the balance is water.
[0008] On the basis of the above scheme, further, the matrix asphalt is one or more of natural asphalt, petroleum asphalt, coal tar asphalt or oil sand asphalt.
[0009] Specifically, the base asphalt is No. 70 base asphalt produced by Xiamen Municipal Engineering Co., Ltd.
[0010] On the basis of the above scheme, further, the water-based epoxy resin is prepared by emulsifying, dispersing or modifying bisphenol A epoxy resin by NN-dimethylethylenediamine and then using water as a medium.
[0011] The purpose of adopting the above technical scheme is to enhance the adhesion and strength of emulsified asphalt in the microstructure of water-based epoxy resin. In emulsified asphalt, water-based epoxy resin is dispersed in the water phase and interacts with the surface of asphalt particles. During the curing process, epoxy groups can chemically react with hydroxyl groups or amino groups in the matrix to form a microscopic cross-linked network structure. This cross-linked structure not only enhances the mechanical strength of the material, but also improves the high and low temperature resistance of the system.
[0012] Preferably, the particle diameter of the waterborne epoxy resin is 0.1-1 μm.
[0013] Specifically, the bisphenol A epoxy resin is E51 epoxy resin.
[0014] On the basis of the above scheme, further, the silicon dioxide content of the alkaline silica sol is 10%-50% of its mass; the alkaline silica sol is prepared by hydrolyzing silicate under alkaline conditions.
[0015] By adopting the above technical scheme, the silica particles in the silica sol can be evenly distributed on the interface of the emulsified asphalt particles to form a reinforced micro-skeleton structure, which effectively enhances the strength, wear resistance and deformation resistance of the asphalt material. In addition, since the silica particles have high hardness and excellent crack resistance, they play a filling and reinforcing role at the micro level, preventing the expansion of micro-cracks in the material under stress, thereby improving the overall durability and fatigue resistance of the material.
[0016] Preferably, the pH value of the alkaline silica sol is 8.5-11.5, and the particle size is 40-150 nm.
[0017] On the basis of the above scheme, further, the emulsifier is one or more of coconut oil-based hydroxyethyl imidazoline, 4-(hydroxymethyl) imidazoline-2-one, 2-(1-hydroxyethyl)-2-imidazoline or 2-[1-(hydroxymethyl)ethyl]oxazoline.
[0018] By adopting the above technical scheme, the cationic emulsifier can adsorb to the surface of asphalt particles through electrostatic action in a low pH environment to prevent aggregation between particles; the non-ionic emulsifier further improves the physical stability of the emulsion by forming a steric hindrance effect and hydrogen bonding. Through the synergistic effect of the emulsifier, the microscopic particle structure formed in the emulsification process is more uniform, the storage stability of the emulsion is significantly improved, and the possibility of particle sedimentation, demulsification or stratification is reduced.
[0019] Preferably, the molecular weight of the emulsifier is 600-3000.
[0020] On the basis of the above scheme, further, the preparation method of the emulsifier is: pentaerythritol glycidyl ether, ethylene oxide and hydroxyimidazoline are prepared by polymerization reaction in a molar ratio of 1:4-12:4-12 under the action of a catalyst; the catalyst is one or more of sodium methoxide, sodium tert-butoxide, sodium ethoxide, lithium aluminum tetrahydride, sodium hydroxide, potassium hydroxide, sodium cyanide or metallic sodium.
[0021] Preferably, the amount of the catalyst is 0.1%-0.3% of the mass of ethylene oxide; the polymerization reaction temperature is 80-200° C., the reaction pressure is 0.2-5 MPa, and the reaction time is 1-3 h.
[0022] On the basis of the above scheme, further, the stabilizer is polyvinyl alcohol or sodium carboxymethyl cellulose.
[0023] Preferably, the stabilizer is polyvinyl alcohol.
[0024] On the basis of the above solution, further, the curing agent is a polyamide curing agent.
[0025] Specifically, the curing agent is a polyamide curing agent of a low molecular weight resin generated by the polycondensation reaction of linoleic acid dimer and aliphatic polyamine.
[0026] The present invention also provides a method for preparing the high-strength composite modified emulsified asphalt material as described above, comprising the following preparation steps: S1. Heat the base asphalt uniformly to 150-160°C; The purpose of adopting the above technical solution is to melt the matrix asphalt into a low-viscosity liquid. During this process, the temperature needs to be precisely controlled to avoid oxidative degradation due to overheating, and proper stirring is required to ensure uniform heating.
[0027] S2, adding a stabilizer and an emulsifier into water and heating it to 60-70° C., adjusting the pH value of the solution to between 2 and 3 while stirring, to obtain a soap solution; S3. After adding soap solution to the rinsed colloid mill, slowly add the heated base asphalt, start the colloid mill for high-speed shearing for 2-5 minutes, and then quickly cool to room temperature to obtain emulsified asphalt; The purpose of rinsing is to prevent impurities in the equipment from interfering with the emulsification process.
[0028] S4, mixing the water-based epoxy resin and the alkaline silica sol uniformly to obtain a composite latex; S5, adding the composite latex to the emulsified asphalt, and shearing it with a high-speed shearing machine for 10-20 minutes to obtain a composite modified emulsified asphalt; The purpose of adopting the above technical solution is to fully mix the composite latex with the emulsified asphalt and ensure that the modifier is evenly dispersed in the asphalt system.
[0029] S6. Evenly mix the composite modified emulsified asphalt and the curing agent to obtain high-strength composite modified emulsified asphalt.
[0030] Preferably, in step S2, the stirring is specifically: stirring at a rotation speed of 300 r / min for 20-30 min; and adjusting the pH value using industrial hydrochloric acid.
[0031] Preferably, in step S3, after adding the soap solution, the colloid mill is started and stirred for 1-2 minutes before slowly adding the base asphalt, and the rotation speed of the colloid mill is 3000-5000r / min.
[0032] The present invention also provides an application of the high-strength composite modified emulsified asphalt material as described above in micro-surfacing pavement.
[0033] Specifically, basalt aggregate and ordinary Portland cement filler are first mixed at room temperature, and then composite modified emulsified asphalt and water are added, mixed and stirred rapidly to obtain a micro-surfacing mixture.
[0034] More specifically, the mass ratio of the basalt aggregate, high-strength composite modified emulsified asphalt, water and ordinary Portland cement filler is 100-110:15-20:1-2:6-6.5.
[0035] Compared with the prior art, the high-strength composite modified emulsified asphalt material provided by the present invention innovatively uses alkaline silica sol and water-based epoxy resin to modify the emulsified asphalt, and forms a three-dimensional cross-linked network through the cross-linking reaction of the water-based epoxy resin and the emulsified asphalt. The addition of silica sol further refines the particles of the emulsified asphalt, enhances the interaction between the particles, and consolidates the strength of the asphalt matrix, so that the emulsified asphalt has significant adhesion and stability, and exhibits higher compressive strength and shear strength after curing. At the same time, the microscopic porosity of the emulsified asphalt is optimized, the permeability of water is reduced, the waterproof performance is enhanced, and the high temperature and low temperature resistance are improved. In addition, the use of common organic solvents (such as solvent-based epoxy resin) in the traditional asphalt modification process is avoided, which is more environmentally friendly. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] In order to solve the problem of how to use epoxy resin and silica sol in combination to improve the strength of emulsified asphalt, the present invention provides the following embodiments and comparative examples.
[0038] Example 1 The raw materials required for Example 1 are expressed in percentage by mass, and their compositions and contents are as follows: 56% matrix asphalt, 1.5% emulsifier, 5% water-based epoxy resin, 5% curing agent, 0.1% stabilizer, 5% alkaline silica sol, and the balance is water.
[0039] Example 1 The preparation method is as follows: S1. Heat the base asphalt uniformly to 153°C to melt it into a low-viscosity liquid; S2, adding a stabilizer polyvinyl alcohol and an emulsifier coconut oil-based hydroxyethyl imidazoline into water and heating to 60° C., stirring at a speed of 300 r / min for 20 min, and during the stirring process, adding industrial hydrochloric acid dropwise to adjust the pH value of the solution to between 2 and 3 to obtain a soap solution; S3. Rinse the colloid mill to prevent impurities in the equipment from interfering with the emulsification process. After adding soap solution to the rinsed colloid mill, stir at a speed of 3000-5000r / min for 1-2min, slowly add the heated base asphalt, start the colloid mill for high-speed shearing, emulsify for 2min, and then quickly cool to 25°C to obtain emulsified asphalt; S4, mixing the waterborne epoxy resin and the alkaline silica sol and stirring until a stable composite latex is formed; S5, adding the composite latex to the cooled emulsified asphalt, and shearing it for 10 minutes using a high-speed shearing machine to obtain a composite modified emulsified asphalt; S6. Stir and mix the composite modified emulsified asphalt and the polyamide curing agent for 10 minutes to obtain a high-strength composite modified emulsified asphalt.
[0040] Example 2 The raw materials required for Example 2 are expressed in percentage by mass, and their compositions and contents are as follows: 58% matrix asphalt, 1.9% emulsifier, 8% water-based epoxy resin, 8% curing agent, 0.2% stabilizer, 7% alkaline silica sol, and the balance is water.
[0041] Embodiment 2 preparation method is as follows: S1. Heat the base asphalt uniformly to 155°C to melt it into a low-viscosity liquid; S2, adding a stabilizer polyvinyl alcohol and an emulsifier coconut oil hydroxyethyl imidazoline to water and heating to 65° C., stirring at a speed of 300 r / min for 25 min, and during the stirring process, adding industrial hydrochloric acid dropwise to adjust the pH value of the solution to between 2 and 3, to obtain a soap solution; S3. Rinse the colloid mill to prevent impurities in the equipment from interfering with the emulsification process. After adding soap solution to the rinsed colloid mill, stir at a speed of 3000-5000r / min for 1-2min, slowly add the heated base asphalt, start the colloid mill for high-speed shearing, emulsify for 3min, and then quickly cool to 25°C to obtain emulsified asphalt; S4, mixing the waterborne epoxy resin and the alkaline silica sol and stirring until a stable composite latex is formed; S5, adding the composite latex to the cooled emulsified asphalt, and shearing it for 10 minutes using a high-speed shearing machine to obtain a composite modified emulsified asphalt; S6. Stir and mix the composite modified emulsified asphalt and the polyamide curing agent for 10 minutes to obtain a high-strength composite modified emulsified asphalt.
[0042] Example 3 The raw materials required for Example 3 are expressed in percentage by mass, and their compositions and contents are as follows: Base asphalt 63%, emulsifier 2%, water-based epoxy resin 10%, curing agent 10%, stabilizer 0.3%, alkaline silica sol 7%, and the balance is water.
[0043] Example 3 The preparation method is as follows: S1. Heat the base asphalt uniformly to 155°C to melt it into a low-viscosity liquid; S2, adding a stabilizer polyvinyl alcohol and an emulsifier coconut oil hydroxyethyl imidazoline to water and heating to 65° C., stirring at a speed of 300 r / min for 25 min, and during the stirring process, adding industrial hydrochloric acid dropwise to adjust the pH value of the solution to between 2 and 3, to obtain a soap solution; S3. Rinse the colloid mill to prevent impurities in the equipment from interfering with the emulsification process. After adding soap solution to the rinsed colloid mill, stir at a speed of 3000-5000r / min for 1-2min, slowly add the heated base asphalt, start the colloid mill for high-speed shearing, emulsify for 4min, and then quickly cool to 25°C to obtain emulsified asphalt; S4, mixing the waterborne epoxy resin and the alkaline silica sol and stirring until a stable composite latex is formed; S5, adding the composite latex to the cooled emulsified asphalt, and shearing it for 15 minutes using a high-speed shearing machine to obtain a composite modified emulsified asphalt; S6. Stir and mix the composite modified emulsified asphalt and the polyamide curing agent for 15 minutes to obtain a high-strength composite modified emulsified asphalt.
[0044] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that when preparing the composite modified emulsified asphalt, the emulsified asphalt is not modified in this comparative example, that is, the emulsified asphalt prepared in step S3 is directly used for the test.
[0045] The remaining raw materials and their proportions and operations are the same as those in Example 1.
[0046] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that when preparing the composite modified emulsified asphalt, this comparative example only performs water-based epoxy resin modification on the emulsified asphalt, that is, only water-based epoxy resin is used in step S4.
[0047] The remaining raw materials and their proportions and operations are the same as those in Example 1.
[0048] The components and contents of the specific embodiments and comparative examples are shown in Table 1 below: Table 1
[0049] The performance tests were performed on the emulsified asphalts obtained in Examples 1-3 and Comparative Examples 1-2: Test standards: "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011) and "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber" (GBT 528-1998).
[0050] The test results are shown in Table 2 below: Table 2 Emulsified asphalt performance test results
[0051] As can be seen from the test results in Table 1 above, the performance test results of Examples 1-3 of the present invention all meet the standards. Needle penetration is an important indicator for measuring the hardness and consistency of asphalt, which indicates the relative viscosity of asphalt under certain conditions. As can be seen from Table 1 above, the needle penetration of Examples 1-3 is significantly lower than that of Comparative Examples 1-2, indicating that the high-strength composite modified emulsified asphalt prepared by the present invention has higher hardness and viscosity; The softening point is the temperature at which asphalt begins to soften under heating conditions, reflecting the temperature stability and heat resistance of asphalt. As shown in Table 1 above, the softening points of Examples 1-3 are significantly higher than those of Comparative Examples 1-2, indicating that the high-strength composite modified emulsified asphalt prepared by the present invention has better heat resistance. Compared with Comparative Examples 1-2, the high-strength composite modified emulsified asphalt prepared in Examples 1-3 has outstanding tensile strength and better ductility.
[0052] The emulsified asphalt prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-2 is applied to the micro-surfacing mixture, and the specific steps are as follows: First, basalt aggregate and ordinary Portland cement filler are mixed at room temperature, and then composite modified emulsified asphalt and water are added, mixed and stirred rapidly to obtain a micro-surfacing mixture; the mass ratio of the basalt aggregate, high-strength composite modified emulsified asphalt, water and ordinary Portland cement filler is 100:18:1.5:6.2.
[0053] The micro-surfacing mixtures prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests according to the standard: "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011).
[0054] Table 3 Test results of micro-surfacing mixture performance
[0055] Note: “ / ” in the table means that the specimen was damaged during the test.
[0056] It can be seen from the test results in Table 3 above that the cohesion of Examples 1-3 is significantly higher than that of the control example. The magnitude of the cohesion can directly reflect the bonding strength between the components in the mixture, and indirectly reflect the shear strength and durability of the mixture. This shows that the high-strength composite modified emulsified asphalt provided by the present invention has better comprehensive performance when used in micro-surfacing mixtures.
[0057] In the mixture, the aromatic components in the resin component can be combined with the aromatic components in the asphalt component, so it has excellent compatibility, so that the asphalt film formed by the asphalt component in the mixture can play a stronger consolidation role. The addition of alkaline silica sol further refines the particles of the emulsified asphalt and may form a protective film on its surface, which enhances the interaction between the particles, and then the aggregate is firmly combined with the mixture as a whole under the wheel load, avoiding the surface of some aggregates from being separated from the overall cover structure of the slurry seal after being run over by the wheels, so it shows better anti-wear performance. In the freeze-thaw cycle test, since the pores of the specimens are saturated with water during the immersion process, the pore water freezes after freezing at 18°C, and the volume expansion causes the micro cracks of the specimens to expand, resulting in a gentle change in the composite modified emulsified asphalt. The reason is that WESEA enhances the adhesion between the emulsified asphalt and the aggregate, increases the interfacial bonding strength, and thus improves the water loss resistance of the micro-surface mixture.
[0058] In summary, the present invention forms a three-dimensional cross-linked network through the cross-linking reaction of water-based epoxy resin and emulsified asphalt, and the addition of silica sol further refines the particles of the emulsified asphalt, enhances the interaction between the particles, and consolidates the strength of the asphalt matrix, so that the emulsified asphalt has significant adhesion and stability, and exhibits higher compressive strength and shear strength after curing. At the same time, the microscopic porosity of the emulsified asphalt is optimized, the permeability of water is reduced, the waterproof performance is enhanced, and the high temperature and low temperature resistance are improved. When applied to micro-surfacing mixtures, its shear strength, durability, bonding with aggregates, and water loss resistance are significantly improved.
[0059] Although the terms such as asphalt, waterborne epoxy resin and silica sol are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional restrictions is contrary to the spirit of the present invention.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-strength composite modified emulsified asphalt material, characterized in that: Calculated by weight percentage, it includes 50%-70% matrix asphalt, 1%-3% emulsifier, 5%-15% water-based epoxy resin, 5%-15% curing agent, 0.1%-0.3% stabilizer, 3%-10% alkaline silica sol, and the balance is water.
2. The high-strength composite modified emulsified asphalt material according to claim 1, characterized in that: The matrix asphalt is one or more of natural asphalt, petroleum asphalt, coal tar asphalt or oil sand asphalt.
3. The high-strength composite modified emulsified asphalt material according to claim 1, characterized in that: The waterborne epoxy resin is prepared by emulsifying, dispersing or modifying bisphenol A epoxy resin with NN-dimethylethylenediamine and then using water as a medium.
4. The high-strength composite modified emulsified asphalt material according to claim 1, characterized in that: The silicon dioxide content of the alkaline silica sol is 10%-50% of its mass; the alkaline silica sol is prepared by hydrolyzing silicate under alkaline conditions.
5. The high-strength composite modified emulsified asphalt material according to claim 1, characterized in that: The emulsifier is one or more of coconut oil-based hydroxyethyl imidazoline, 4-(hydroxymethyl) imidazoline-2-one, 2-(1-hydroxyethyl)-2-imidazoline or 2-[1-(hydroxymethyl)ethyl]oxazoline.
6. The high-strength composite modified emulsified asphalt material according to claim 1, characterized in that: The preparation method of the emulsifier comprises the following steps: subjecting pentaerythritol glycidyl ether, ethylene oxide and hydroxyimidazoline to a polymerization reaction at a molar ratio of 1:4-12:4-12 under the action of a catalyst; the catalyst is one or more of sodium methoxide, sodium tert-butoxide, sodium ethoxide, lithium aluminum tetrahydride, sodium hydroxide, potassium hydroxide, sodium cyanide or metallic sodium.
7. The high-strength composite modified emulsified asphalt material according to claim 1, characterized in that: The stabilizer is polyvinyl alcohol or sodium carboxymethyl cellulose.
8. The high-strength composite modified emulsified asphalt material according to claim 1, characterized in that: The curing agent is a polyamide curing agent.
9. A method for preparing a high-strength composite modified emulsified asphalt material according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1. Heat the base asphalt uniformly to 150-160°C; S2, adding a stabilizer and an emulsifier into water and heating it to 60-70° C., adjusting the pH value of the solution to between 2 and 3 while stirring, to obtain a soap solution; S3. After adding soap solution to the rinsed colloid mill, slowly add the heated base asphalt, start the colloid mill for high-speed shearing for 2-5 minutes, and then quickly cool to room temperature to obtain emulsified asphalt; S4, mixing the water-based epoxy resin and the alkaline silica sol uniformly to obtain a composite latex; S5, adding the composite latex to the emulsified asphalt, and shearing it for 10-20 minutes using a high-speed shearing machine to obtain a composite modified emulsified asphalt; S6. Add a curing agent to the composite modified emulsified asphalt, mix well, and obtain a high-strength composite modified emulsified asphalt.
10. Use of the high-strength composite modified emulsified asphalt material according to any one of claims 1 to 8 in micro-surfacing pavement.
Citation Information
Cited By
High-viscosity emulsified asphalt and preparation method thereof
CN122146076A